2023
DOI: 10.3390/nano13081415
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancing Effect of Stable Oxygen Functional Groups on Porous-Carbon-Supported Pt Catalysts for Alkaline Hydrogen Evolution

Abstract: The oxygen functionalization of carbon materials has widely been employed to improve the catalytic performance of carbon-supported Pt (Pt/C) catalysts. Hydrochloric acid (HCl) has often been employed to clean carbons during the preparation of carbon materials. However, the effect of oxygen functionalization through a HCl treatment of porous carbon (PC) supports on the performance of the alkaline hydrogen evolution reaction (HER) has rarely been investigated. Herein, the impact of HCl combined with the heat tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The materials showed morphologies and structures with irregular grain, characteristic of porous carbon. Such large visible pores would provide the electrolyte with abundant accessible areas for better ion diffusion. , The EDS maps in Figure d–f revealed the presence of C, N, and O elements, demonstrating the successful introduction of N element and uniform distribution of N and O elements in the NPC sample.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The materials showed morphologies and structures with irregular grain, characteristic of porous carbon. Such large visible pores would provide the electrolyte with abundant accessible areas for better ion diffusion. , The EDS maps in Figure d–f revealed the presence of C, N, and O elements, demonstrating the successful introduction of N element and uniform distribution of N and O elements in the NPC sample.…”
Section: Resultsmentioning
confidence: 94%
“…Such large visible pores would provide the electrolyte with abundant accessible areas for better ion diffusion. 32,33 The EDS maps in Figure 1d The crystal structures of PC, NPC, and NPC-1 were studied by XRD. As illustrated in Figure 2a, three samples exhibited a hump-like diffraction peak located at 2θ angle of 23°, assigned to typical amorphous carbon.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…The ratio of C–C, C–O, and C–OO and CO peaks for CB carbon support is determined to be 74.7%, 17%, and 8.3%, respectively, while for CB 300 carbon support, the ratios are 64.6%, 20%, and 15.4%. These results indicate that the chemical state of carbon black changed after heat treatment at 300 °C, with CB 300 carbon support exhibiting a higher proportion of oxygen-containing functional groups, which promotes the adsorption of Pt particles. , As shown in Figure d, following the standard O 1s XPS fitting procedure, we analyzed the O 1s XPS spectra of carbon black before and after heat treatment at 300 °C. We found that the oxygen vacancies (O v ) of carbon black decreased dramatically after heat treatment at 300 °C, which may be due to the fact that for toner, the heat treatment process may cause changes in the structure and chemical composition of the substance, resulting in a decrease in the number of O v on the surface of the toner, which in turn leads to a dramatic decrease in the O v . …”
Section: Resultsmentioning
confidence: 99%
“…Suitable carbon supports would not only act as physical carriers to anchor and disperse active Pt species but also should interact with supported Pt to influence the HER performance of the Pt/C catalyst. The surface properties of carbon supports would affect the catalytic activity and stability of Pt/C catalysts, ,, where oxygen functionalization of carbon supports could increase the interaction between carbon supports and Pt particles, resulting in enhanced electrochemical stability. , The electroactivity of Pt/C can be enhanced by treating the carbon supports with basic or neutral agents, while treatment by acid agents may delay Pt/C catalysts . The intrinsic defects of carbons may also play a vital role in the catalytic performances. , The presence of intrinsic defects in carbon supports could result in asymmetric charge distribution, change in geometrical configuration, and distortion of the electronic structure. , The presence of intrinsic defects in carbons could act as efficient active sites to promote the catalytic reactions during oxygen reduction reaction (ORR), CO 2 reduction, and HER. Therefore, the construction of intrinsic carbon defects can effectively enhance the electrochemical performances of carbon materials. For instance, various studies have shown that intrinsic carbon defects could efficiently enhance the electrocatalytic CO 2 reduction, while pentagon defect-rich carbon may possess good ORR activity .…”
Section: Introductionmentioning
confidence: 99%
“…The surface properties of carbon supports would affect the catalytic activity and stability of Pt/C catalysts, 11,15,16 where oxygen functionalization of carbon supports could increase the interaction between carbon T h i s c o n t e n t i s supports and Pt particles, resulting in enhanced electrochemical stability. 17,18 The electroactivity of Pt/C can be enhanced by treating the carbon supports with basic or neutral agents, while treatment by acid agents may delay Pt/C catalysts. 19 The intrinsic defects of carbons may also play a vital role in the catalytic performances.…”
Section: Introductionmentioning
confidence: 99%